Fever of unknown origin in a male patient with systemic lupus erythematosus - Duminda Bandara Basnayake; Thamara Kannangara; Laknath Welagedara; Vindhya Bandara; Janitha Herath (Babol University of Medical Sciences, 2017)
Background: Systemic lupus erythematosus (SLE) is an inflammatory autoimmune disorder which is uncommon in men. It has a wide variety of clinical presentations. Case Report: We report a 21-year-old male presented with one month history of fever, loss of appetite, weight loss and reduced hair growth with an examination revealing an oral ulcer, cervical and axillary lymphadenopathy simulating hematological malignancy. Investigations showed pancytopenia, positive anti-nuclear factor and double-stranded DNA, high erythrocyte sedimentation rate with normal C-reactive protein levels and hypocomplementemia. The diagnosis of systemic lupus erythematosus was made and treatment with oral prednisolone conferred a dramatic clinical and biochemical improvement within one week. Conclusion: In the evaluation of fever of unknown origin, one should be guided by the presenting symptoms and signs of a patient and even though uncommon, SLE is a worthwhile diagnosis to investigate even in a male patient if the clinical picture is suggestive.